Consumption trends of steel and aluminium in the context of decarbonization - Torsten Hummen; Katrin Ostertag (Fraunhofer-Institut für System- und Innovationsforschung ISI, 2015)
In order to be able to analyze future ecological as well as economic aspects of the climate protection potential through decarbonisation of German industries, the aluminium and steel industry must be investigated in detail. The construction and mechanical sectors are among the biggest consumers of aluminium and steel in Germany. Consequently this paper examines the future consumption trends of steel and aluminium for these sectors. To project the consumption trends for a long-term perspective (2050), a simple regression model is developed. The model consists of four steps. First, the future German GDP is projected. Secondly, overall aluminium and steel consumption is calculated based on a linear regression function with GDP as the explanatory variable. Third, the future sector shares of each material are calculated with the help of a trend analysis. Finally, the results of steps two and three are combined to derive the future material consumption of each sector by multiplication. According to the simple regression model developed in the paper the consumption of both analyzed materials will increase until 2050 - in case of steel by 41 % and of aluminium by 95 %. The construction sector will increase its absolute amount of steel consumption, but reduce its aluminium consumption. These consumption patterns are the exact opposite for the mechanical engineering sector, albeit on a different scale. The presented results show their plausibility when compared to those in the literature. Although a high uncertainty implies the results due to the lack of data, especially in the case of the projected steel consumption trends.
urn:nbn:de:0011-n-3319705
Keywords: 330